Євангельські християни-баптисти в УРСР (середина 1940 – середина 1980-х рр.): взаємини з владою, особливості та трансформації релігійного життя - Бондарчук, П. (Український історичний журнал, 2018)
Висвітлюється політика радянської влади щодо євангельських християнбаптистів та її зміни в повоєнний час, у роки хрущовського наступу на релігію й у період «застою». Розглянуто об’єднання з баптистами євангелістів,
частини п’ятидесятників, менонітів та інших протестантських деномінацій, основні аспекти внутрішньоконфесійного життя цієї релігійної течії, а саме підпільні форми існування євангельсько-баптистських громад, які
перебували поза контролем органів влади. Висвітлено антирелігійні дії радянського режиму, різні форми переслідувань, зокрема незаконне закриття
молитовних будинків, порушення прав віруючих, формування неґативної суспільної думки, притягнення вірян до адміністративної та кримінальної відповідальності. Порушено питання розколу у Союзі ЄХБ, причиною якого став
спротив віруючих державній антирелігійній політиці. Розглянуто мережу релігійних організацій в УРСР, кількісний склад та соціально-демографічні характеристики. Особливу увагу приділено релігійній поведінці віруючих.
Висвітлено відвідування ними молитовних будинків та нелеґальних молитовних зібрань, участь у богослужіннях на великі свята, у релігійних демонстраціях тощо. The article examines the religious life of Evangelical Baptist Christians during the
period from the mid-1940s to the mid-1980s. The author analyzes the religious policy
of the Soviet power concerning Evangelical Baptist Christians and its changes during
the postwar time, in the years of N.Khrushchev’s assault on religion, throughout the
era of stagnation; shows the relationship between the Soviet state and Evangelical
Baptist Christians. The article considers the association of the Baptists with the
Evangelists, the Pentecostals, the Mennonites and other Protestant currents; the
main aspects of the intra-confessional religious life of this religious current, the
underground forms of the existence of the Evangelical Baptist Christians communities
that were beyond the control of the Soviet power. The antireligious actions of the
Soviet regime, various forms of oppression of religious communities and believers,
in particular illegal closures of prayer houses, violation of the believers’ rights, the
formation of negative public opinion regarding this religious current, administrative
proceedings against the believers and their criminal prosecution are elucidated. The
article touches the issue of the split in the Union of the EBCh, which was caused
by the opposition of the believers to the anti-religious policy of the state, it traces
how part of the believers stood in the opposition to the leadership of the All-Union
Council of the EBCh, and later formed an illegal church authority – the Council of
Churches of EBCh. The network of religious organizations in the Ukrainian SSR, the
quantitative composition of the believers, and their socio-demographic characteristics
are described. Special attention is given to the religious behaviour of the believers.
Believers’ attendance of prayer houses and illegal prayer meetings, their participation
in worship on big holidays and in religious demonstrations, etc are elucidated.